Rare and aggressive tumor in an unexpected patient - Kocabaş, Seyhan; Özen, Mehmet; Oklar, Murat; Yazıcıoğlu, Titap (Klinika Oczna / Acta Ophthalmologica Polonica, 2022)
A 56-year-old female patient presented with complaints of medial swelling in her left upper eyelid, growing rapidly for 3 months. She stated that she had received local antibiotic therapy and steroid therapy in two different centers with the diagnosis of chalazion, but with no benefit. For differential diagnosis, we planned a surgical excision of the tumor and chose the Cutler-Beard technique. The pathological and immunohistochemical results of the mass were reported as Merkel cell carcinoma without lymphovascular or perineural invasion. For tumors with high risk of distant metastasis such as MCC, early diagnosis, choosing the appropriate surgical technique, and adjuvant treatments have a positive effect on quality of life and survival.